2018
DOI: 10.1038/s41598-018-20568-x
|View full text |Cite
|
Sign up to set email alerts
|

Tunable phonon blockade in quadratically coupled optomechanical systems

Abstract: We theoretically investigate the phonon statistics of a quadratically coupled optomechanical system, in which an effective second-order nonlinear interaction between an optical mode and a mechanical mode is induced by a strong optical driving field on two-phonon red-sideband resonance. We show that strong phonon antibunching can be observed even if the strength of the effective second-order nonlinear interaction is much weaker than the decay rates of the system, by driving the optical and mechanical modes with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 46 publications
(37 reference statements)
1
16
1
Order By: Relevance
“…The effective nonlinear coupling between the optical and mechanical modes in a quadratically coupled optomechanical system can be enhanced by a strong driving optical field as shown in Refs. [54,56,57,59]. Different from the previous studies [54,56], we find that there is an optimal value of the effec-tive nonlinear coupling strength for photon blockade before reaching the strong nonlinear coupling regime, and both photon and phonon blockades can be observed in a quadratically coupled optomechanical system with the same parameters.…”
Section: Introductioncontrasting
confidence: 85%
See 1 more Smart Citation
“…The effective nonlinear coupling between the optical and mechanical modes in a quadratically coupled optomechanical system can be enhanced by a strong driving optical field as shown in Refs. [54,56,57,59]. Different from the previous studies [54,56], we find that there is an optimal value of the effec-tive nonlinear coupling strength for photon blockade before reaching the strong nonlinear coupling regime, and both photon and phonon blockades can be observed in a quadratically coupled optomechanical system with the same parameters.…”
Section: Introductioncontrasting
confidence: 85%
“…It has been shown that photon blockade can be realized in the optomechanical system with different structures, such as strongly coupled optomechanical systems at single-photon level [41][42][43][44][45][46][47], multimode optomechanical systems [48][49][50][51], squeezed optomechanical systems [52,53], quadratically coupled optomechanical system driven by a strong optical field [54]. Recently, strong phonon antibunching was proposed in a quadratically coupled optomechanical system [55][56][57] and this provides another possible way to generate single phonons in the optomechanical system. However, the realization of both photon blockade and phonon blockade in one optomechanical system with the same parameters has not been considered yet.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many researches have been carried out on the optomechanical system, which explores the quantum-mechanical interaction via the radiation pressure. So far, many promising applications of the optomechanical system have been reported, such as ground state cooling [1][2][3][4][5][6], photon blockade [7][8][9][10][11], optical switching and buffer [12][13][14][15][16],detector [17][18][19][20][21][22], and so on. One recent research is spin detection which improves the force sensitivity by almost 2 orders of magnitude than with tensioned resonators [21].…”
Section: Introductionmentioning
confidence: 99%
“…Physically, the strong phonon antibunching for UCPNB is based on the destructive interference between different paths for two-phonon excitation 8 , that UCPNB is usually realized by coupling an auxiliary system to the mechanical mode. Recently, UCPNB was predicted in many different systems, e.g., resonant coupled NAMR-qubit system 8 , coupled nonlinear mechanical resonators 15,16 , quadratically optomechanical system 17 , and hybrid optomechanical system 18 .…”
Section: Introductionmentioning
confidence: 99%